Mineralogical, geochemical and lead isotopic analysis of the lead mineralization of the Skorpion Deposit, south western Namibia - Uazeua, Kakunauua (Rhodes University, Faculty of Science, Department of Geology, 2019)
The Skorpion none-sulphide Zinc Deposit is located in the para-autochtonous Port Nolloth Zone of the Gariep Belt, which overlays the Lower-Proterozoic Orange River Group basement rocks (Corrans et al., 1993). Situated in close proximity to the larger Rosh Pinah Zn-Pb deposit, the Skorpion Deposit contained a resource of 24.6 Mt at 10.6 % Zn and unquantified Cu and Pb prior to mining. To date, zinc has been the only metal exploited, with minor amounts of copper as a by-product. This study aims at understanding the mineralogical composition of the Skorpion lead mineralization and understanding the relationship between lead and the major metals such as zinc and copper in order to form a basis for further work that could determine the potential of processing lead as a by-product. As part of the study, work was also done on lead isotopes mainly with the aim of understanding the mineralization genesis and to determine the differences between the Skorpion and Rosh Pinah deposit which rationalize the inferior economic potential of the Skorpion lead mineralization. Results of the study have shown that majority of the lead mineralization is hosted by the felsic metavolcanics as galena and subordinately in the metasiliciclastics as pyromorphite, a lead manganese phosphate. In terms of the mineral textures, the lead minerals appear to be mainly secondary phases that have been remobilized and reprecipitated around pyrite, within pyrite cracks and intergrown with minerals such as chalcocite and greenockite. Lead has been mainly concentrated along fault zones. The elevated pyromorphite concentrations tend to occur within gossanous zones in close association with iron and manganese oxides. These textures represent supergene enrichment of a sulphide proto ore. However, contrary to copper and zinc mineralization, lead was not remobilized far from the proto ore merely as a function of its poor mobility in acidic fluids (Reddy et al., 1995). This substantiates the concentration of secondary lead in the felsic metavolcanics and to a much lesser extent, in the metasiliciclastics. Both secondary zinc and copper were reprecipitated in the metasiliciclastics, further away from the sulphide proto ore, hosted mainly by the felsic metavolcanics. The average lead isotope ratios of 206Pb/204Pb (17.26), 207Pb/204Pb (15.60) and 208Pb/204Pb (37.42) resemble results provided by Frimmel (2004) for both the Skorpion and Rosh Pinah deposits. For the Skorpion samples from Frimmel (2004) had the following average ratios: 206Pb/204Pb (17.29), 207Pb/204Pb (15.59) and 208Pb/204Pb (37.51). The Rosh Pinah samples had the following average ratios: 206Pb/204Pb (17.17), 207Pb/204Pb (15.61) and 208Pb/204Pb (37.45). These results indicate lead derivation from the lower 2.0 Ga Eburnean pre-Gariep basement in agreement with and Frimmel et al. (2004). The host felsic metavolcanics might have been derived from melting of the basement rocks during the formation of the Adamastor Ocean. In comparison to the Rosh Pinah deposit lead isotope signatures, the Skorpion lead isotopes overlap with the Rosh Pinah deposit isotopes, but have a much narrower range. This is an indication of a much shorter lived and potentially faster mineralization event contrary to the SEDEX type Rosh Pinah deposit. The smaller tonnage of the Skorpion deposit, its inferior lead concentrations and the elevated radiogenic lead isotopes point toward a VMS deposit which was formed in a small graben fed by shallow conduits during a short lived mineralization event. Sedimentary rocks covered the forming deposit at a fast rate and impaired the deposit advancement. The interaction between the upper crustal rocks and the mineralizing fluids is what may have resulted in the elevated radiogenic lead signature. In contrast to this, SEDEX deposits such as the Rosh Pinah Deposit, are generally fed by deep seated conduits that allow more longer lived leaching of metals from the underlying basement rocks and generally allow minor influence from upper crustal rocks.
Keywords: Zinc ores -- Namibia; Formations (Geology) -- Namibia; Mineralogy -- Namibia; Lead -- Metallurgy -- Namibia; Lead -- Isotopes -- Namibia